Identifikasi Nilai Kekasaran Permukaan pada Pemesinan Paduan Magnesium - Gusri Akhyar Ibrahim (JURNAL MECHANICAL, 2014)
The using of magnesium alloy, as alternative to iron and steel, is becoming more popular in the manufacturing industries. Magnesium and its alloys were classified as lighter material and also available in a quite large quantity in this world. Some of machined componens, included automotive and aerospace componens were produced by cutting, which is known as machining process. The machining process done in several conditions doe to the pharamater or factor in machining process. The main factors in machining process are  feed rate, cutting speed, machining condition and deep of cutting. The purpose of this research is to investigate the influence of cutting pharameter to the surface roughness of magnesium, when machined using milling process and supplied with cooling air from vortex tube cooler. Cutting pharameters  used in this research are feed rate and cutting speed. Feed rate used was three levels, those are 0,15 mm/rev, 0,20 mm/rev, and 0,25 mm/rev. Cutting speed used also three levels, those are 23,18 m/min, 32,15 m/min and 42,7 m/min. Cooling air is released from vortex tube cooler with 15 oC of temperature. The result of this research is found that feed rate affected signicantly on surface roughness value. The surface roughness value increased with increasing of the feed rate level. An other han, the surface roughness  value is also affected wear on the edge of the cutting tool. The wear on the cutting tool contributed to the changes of  nose radius (become bigger), so increase the surface roughness value.Keywords: magnesium material, surface roughness, milling, cutting pharameter, cooling air.